Informatividade da despesa fiscal - Medeiros, Jislene Trindade (2022)
This research seeks to deepen the knowledge about the informativeness of fiscal expenditure for capital market users. For this purpose, three articles were developed with the purpose of filling gaps identified in the literature that investigates the informativeness of the tax information. In the first article, the effect of accounting-tax compliance is examined on the informativeness of tax expenditure in a sample consisting of 17,014 companies from 38 countries, from 2000 to 2019. The results indicate that the more aligned the accounting standards and tax rules of a country, the less informative is the tax expense of companies. However, the findings showed that the level of accounting-tax compliance of the country increases the informativeness of fiscal expenditure that is incremental to profit. When if jointly consider the effect of accounting-tax compliance and tax enforcement of the country in the informativeness of the tax expenditure, the results demonstrate that the informativeness of the surprise in tax expenditure is greater in countries with greater accounting-tax compliance and tax enforcement. The second article brings together a sample consisting of 4,775 companies from 35 countries, from 2001 to 2019, and investigates the relationship between the surprise in fiscal expenditure and the future accuracy of analysts' earnings forecast and how the country's tax enforcement changes this relationship. The results provide evidence that the surprise in fiscal expenditure is incrementally relevant to the earnings surprise when explaining future analyst errors. Furthermore, it was found that analysts are unable to incorporate into their forecasts the information contained in the fiscal expenditure surprise and that the inefficiency of analysts in process and incorporate information about the expense surprise into your earnings forecasts taxation can be minimized in markets with a higher level of monitoring and inspection by the tax authority. In the third article, we analyze how the value relevance of surprise in tax expenditure is affected in companies that manage earnings to meet earnings benchmarks, using data from 73,737 companies from 38 countries, in the period of 2000 to 2019. The results indicate that the informativeness of the surprise in fiscal expenditure is intensified in companies suspected of managing earnings to meet or exceed analysts' earnings expectations and avoid reporting losses, and that suspicious companies of managing earnings through income tax expense showed lower future returns. In addition, it was found that the informational power of surprise in expenditure tax intensifies in companies suspected of managing results to reach or exceed analyst consensus prediction by reducing the estimated Effective Taxe Rate (ETR) from the third to the fourth quarter. In general, the research findings demonstrate that accounting-tax compliance and earnings management affect the informativeness of the fiscal expenditure, and suggest that current and future discussions on expenditure informativeness tax are expanded, considering the importance of tax enforcement for the quality of the fiscal information necessary to form the expectations of financial analysts about future performance.